Edukasi Kesehatan Masyarakat Tentang Hiperkolestrolemia Pada Lansia Di Gg. Purnama Banjarmasin: Edukasi Kesehatan Masyarakat Tentang Hiperkolestrolemia Pada Lansia Di Gg. Purnama Banjarmasin - Ra'uf, Muhammad; Noor Lisani Safitri; Yusuf Tajiri, Muhammad; Alya Farrah Izzati; Mahdatun Nafisah; Fani Tatun Habibah; Dewi Sri Utami; Muhammad Yusuf Tajiri (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2025)
Hypercholesterolemia is a significant health problem in Indonesia and tends to increase with age, particularly among the elderly. The low level of knowledge among the elderly about the causes, signs and symptoms, and prevention of high cholesterol is the background to this community service activity. The goal of this activity is to increase the elderly's knowledge about hypercholesterolemia through health education. The method used in this activity included an interactive lecture, a question-and-answer session, and the distribution of informative leaflets. This activity took place on May 7, 2025, at Purnama Mountain, Banjarmasin. Eleven elderly participants participated in the activity, with evaluation conducted through direct observation and discussion. The results of the activity showed a significant increase in participants' understanding during the Q&A session conducted by the community service provider. 100% of participants understood the definition of hypercholesterolemia, 75% understood the causes and symptoms, and 80% understood how to prevent it. The conclusion of this activity indicates that direct health education can increase the elderly's awareness and knowledge about high cholesterol. Therefore, it is recommended that similar activities be held regularly as a promotional and preventive effort within the elderly community, to reduce the risk of degenerative diseases in old age.